Ecological restoration should be redefined for the twenty‐first century. Issue 5 (29th June 2017) - Martin, David M.
Abstract : Forty years ago, ecological restoration was conceptualized through a natural science lens. Today, ecological restoration has evolved into a social and scientific concept. The duality of ecological restoration is acknowledged in guidance documents on the subject but is not apparent in its definition. Current definitions reflect our views about what ecological restoration does but not why we do it. This viewpoint does not give appropriate credit to contributions from social sciences, nor does it provide compelling goals for people with different motivating rationales to engage in or support restoration. In this study, I give a concise history of the conceptualization and definition of ecological restoration, and I propose an alternative definition and corresponding viewpoint on restoration goal‐setting to meet twenty‐first century scientific and public inquiry.